The Mosquito - Jorge R. Rey (EDIS, 2011)
Mosquitoes are some of the most versatile organisms on earth. They can reproduce in virtually any natural or man-made deposit of water and have been found in mines deep below the surface, in mountain peaks, in highly polluted water bodies, in snow pools, and even in crab holes. Although they can be annoying and some are serious health threats, they can play an important role in natural communities, particularly as filter feeders in aquatic communities, and as a food source in both aquatic and terrestrial food chains. Learn more in this revised 7-page fact sheet by Jorge R. Rey, published by the UF/IFAS Department of Entomology and Nematology, July 2011.